2019
DOI: 10.1097/md.0000000000015749
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy with anlotinib for patient with recurrent glioblastoma

Abstract: Rationale: Glioblastoma (GBM) is the most aggressive malignant brain tumor in adults. The first choice for GBM is surgery, and followed by a combination of radiotherapy and chemotherapy. There are limited treatments for patients with recurrent GBM. Relapsed patients usually have a worse prognosis, and with a median survival time of <6 months. Anlotinib is a novel small molecule multi-target tyrosine kinase inhibitor that can inhibit tumor angiogenesis and inhibit tumor cell growth. This drug has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…A meta-analysis showed that the combination of bevacizumab and chemotherapy in the treatment of recurrent GBM significantly improved the progression-free survival and objective response rate but did not extend the OS compared with single-agent bevacizumab [18]. In cases in which standard regimens fail for patients with relapsed GBM, targeted therapies are limited [2]. Molecular markers of GBM are needed to improve personalized diagnosis and treatment and to better understand the biology to facilitate the development of new therapies [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis showed that the combination of bevacizumab and chemotherapy in the treatment of recurrent GBM significantly improved the progression-free survival and objective response rate but did not extend the OS compared with single-agent bevacizumab [18]. In cases in which standard regimens fail for patients with relapsed GBM, targeted therapies are limited [2]. Molecular markers of GBM are needed to improve personalized diagnosis and treatment and to better understand the biology to facilitate the development of new therapies [1].…”
Section: Discussionmentioning
confidence: 99%
“…The preferred treatment for GBM is surgery, and subsequent treatment is a combination of radiotherapy and chemotherapy. For patients with recurrent GBM, targeted therapies are limited [2][3][4]. Molecular markers of GBM are needed to improve personalized diagnosis and treatment and to better understand the biology of the disease to facilitate the development of new therapies [1].…”
Section: Introductionmentioning
confidence: 99%
“…Lv et al published the rst case report of the administration of 12 mg anlotinib to an rGBM patient. The patient achieved a PR after 26 days, but the tumour progressed in two months [4]. Wang et al reported a recurrent GBM patient with an FGFR-TACC3 fusion who was administered anlotinib 12 mg and temozolomide 100 mg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Anlotinib is a novel tyrosine kinase inhibitor that targets VEGFR1/2/3, PDGFR, FGFR1/2/3/4, c-Kit, and Ret. It has been reported to have a promising effect on tumour control in an rGBM case report [4]. However, as a salvage treatment, failure ultimately occurs.…”
Section: Introductionmentioning
confidence: 99%
“…The same large scale study identified 9 EGFR-related pathways which can be targeted by FDA-approved drugs such as Anlotinib ( 83 , 84 ). Anlotinib main use in cancer was already established to treat aggressively, drug-resistant tumors such as glioblastoma ( 85 ); Poziotinib ( 86 88 ). Other available EGFR-targeting molecules include Dacomitinib ( 89 ) and cationic polyamidoamine dendrimers ( 90 ).…”
Section: Pathway-based Drug Repurposingmentioning
confidence: 99%